ANALISIS KEPUTUSAN PEMBELIAN TANAMAN HIAS DAUN PADA LINSY NURSERY KOTA BEKASI - Ardisela, Dawud; Lutfiadi, Ridwan; Afrilian Sarmudin, Suryadimatha Dwi (Fakultas Pertanian Universitas Islam 45 (UNISMA) Bekasi, 2024)
Floriculture is a type of commodity from horticulture such as cut flower ornamental plants, potted plants and garden decoration plants. Linsy Nursery is one of the ornamental plant businesses in Bekasi City which focuses on the ornamental plant business. This study aims to (1) determine and analyze the effect of the marketing mix partially on purchasing decisions for leaf ornamental plants at Linsy Nursery, and (2) determine and analyze the effect of the marketing mix simultaneously on purchasing decisions for leaf ornamental plants at Linsy Nursery. The method used in this research is a survey method and then will be analyzed using descriptive quantitative analysis with multiple regression analysis tools. The sampling technique used in this study is using non probability sampling technique with convenience sampling method as many as 60 respondents. The results of this study indicate that the product has a significant effect on purchasing decisions for leaf ornamental plants, the price has a significant effect on purchasing decisions for leaf ornamental plants, the place has no significant effect on purchasing decisions for leaf ornamental plants.